The management of tetralogy of Fallot after corrective surgery - Tretter, Justin; Morello, Melissa; Chaudry, Anisa; Veldtman, Gruschen (SA Heart Journal, 2018)
With the success of contemporary medical and surgical management in congenital heart disease (CHD), adults with repaired CHD now often outnumber their paediatric equivalents. Tetralogy of Fallot (TOF) has paved the way, not only in the management of native CHD, but also in the management of its repaired form. In this review, we discuss the current surveillance and management of adults with repaired TOF, highlighting outcomes related to these practices.